The Role of the NMDA Receptor in the Anticonvulsant Effect of Ellagic Acid in Pentylenetetrazole-Induced Seizures in Male Mice - Mohammad Rahimi-Madiseh; Zahra Lorigooini; Shakiba Nasiri Boroujeni; Marziyeh Taji; Hossein Amini-Khoei (Behavioural Neurology)
Background and Aim. Epilepsy is the most common neurological disorder after stroke. Ellagic acid (EA) has been shown to possess neuroprotective effects. The N-methyl-D-aspartate receptor (NMDA-R) is involved in the pathophysiology of seizure. We aimed to evaluate the possible involvement of NMDA-R in the anticonvulsant effect of EA in pentylenetetrazole- (PTZ-) induced seizures in male mice. Methods. In this experimental study, 64 mice were divided into 8 groups and received the following: normal saline; EA at doses of 6.25, 12.5, and 25 mg/kg; NMDA agonist at a dose of 75 mg/kg; NMDA antagonist (ketamine) at a dose of 0.5 mg/kg; an effective dose of EA plus NMDA agonist; and a subeffective dose of EA plus ketamine. We induced seizure using intravenous administration of PTZ. 60 minutes before induction of seizure, drugs were administrated. Duration lasts to seizure-induced was measured. Finally, the gene expression of NMDA receptor subunits (Nr2a and Nr2b) was assessed in the prefrontal cortex. Results. Results showed that EA increased the seizure threshold and decreased the expression of Nr2a and Nr2b. We determined that ketamine potentiated and NMDA attenuated the effects of subeffective and effective doses of EA. Conclusion. EA probably via attenuation of the NMDA-R pathway possesses an anticonvulsant effect in PTZ-induced seizure in mice.